Pendekatan Bid’ah dan Ijtihad dalam Pembelajaran: Mengoptimalkan Kemampuan Berpikir Kreatif Peserta Didik - Moh. Muslih (Edukasia Islamika, 2018)
This paper offers the concept of ‘creative education’ by employing an Islamic approach. In the Islamic perspective, creative education highlights two concepts, namely: “bid’ah” and “ijtihad”. The meaning of these two concepts leads to several debates. This present study, therefore, tries to describe both the concepts so as to develop students’ creative thinking skills in teaching and learning processes. This study promotes several endeavors that can be done by teachers to enhance the skills. Firstly, the teachers should be able to synergize their students’ potential in terms of “ruh”, “nafs”, “qalb”, and “aql” so that they emerge as individuals with the power of “mujtahid”. Secondly, they have to be capable of providing their students with an “ijtihadi” stimulus that may trigger the students’ critical thinking skills by stimulating them to address questions. Thirdly, the teachers are expected to provide their students with chances of having ijtihad to explore lots of received information and new knowledge and convey their ideas and thoughts in a public space. Another effort is that they are expected to be able to manage meaningful opportunities to their students in order to perform creative thinking. It illustrates that the students may deliver a wide array of perspectives for a certain issue discussed. Finally, the teachers demonstrate positive appreciation for all the students’ responses by regarding the principle that they attain two points for their appropriate response and one point for their inappropriate one dealing with the result of the students’ ijtihad